The Influence of Organizational Climate on Organizational Citizenship Behavior (OCB) among Millennial Employees with Work-Life Balance as Moderator - Liliana , Anggie; Tentama, Fatwa (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2025)
Work problems for millennial employees are increasingly complex and the values accepted by the generation tend to conflict with organizational citizenship behavior (OCB). Therefore, this research aimed to create and evaluate a theoretical framework that elucidated the impact of organizational climate on the OCB of millennial workers, with work-life balance as a moderator. A total of 384 millennial employees were obtained using purposive quota sampling. The data obtained were related to organizational climate, OCB, and work-life balance. Additionally, a quantitative method was adopted using data analysis through a structural equation model (SEM) and partial least squares path modeling (PLS-SEM). The results showed that the proposed model concerning the influence of organizational climate on citizenship behavior, with work-life balance serving as a moderating variable was consistent with empirical evidence. Organizational climate and work-life balance had a positive and highly significant impact on citizenship behavior. Furthermore, work-life balance effectively moderated the relationship between organizational climate and citizenship behavior of millennial employees. The implications of this research suggested that the model served as a valuable reference and could be implemented to address the challenges associated with OCB.